SPECIAL CHARACTERISTICS OF AERODYNAMIC PROPERTIES OF UNMANNED AIRCRAFT WITH THE HIGH-ASPECT-RATIO WING - O. Е. Lukyanov; A. V. Ostrovoy; M. A. Mensez Soto; Y. A. Klimov; V. G. Shakhov (Научный вестник МГТУ ГА)
The main technical and economic characteristics of the future aircraft are introduced at the early stages of the design process. The high responsibility of these stages is explained by the necessity to make more than 70% of the conceptual decisions on the project, and the mistakes made at this moment, as well as various inaccuracies can entail great economic costs when they are revealed and corrected at later stages of the project development. To reduce the design risks of obtaining an uncompetitive aircraft, there is a need to increase the efficiency of the preliminary design stage targeted to increasing the accuracy and reliability of the results obtained. Special attention should be paid to methods for determining the aerodynamic properties of an aircraft.An evaluation technique for the aerodynamic properties of aircraft with high-aspect-ratio wing was considered, taking the static aeroelasticity into account. The technique is intended for the initial stages of design. The calculation of elastic deformations of the wing for the analysis of the aerodynamic properties of aircraft is provided in order to improve the accuracy of the results and, as a consequence, the accuracy of the choice of the aircraft shape. The application of the technique may allow to increase the efficiency of the preliminary design stage of aircraft. The technique is based on numerical multidisciplinary mathematical modeling using the discrete vortex method and the topology optimization algorithm based on the variable density body model. The main feature of the technique is the use of the algorithm of topology optimization, which makes it possible to determine the elastic-strength characteristics of the full-tension wing design under the conditions of the initial stages of design, when the power circuit is still unknown. Using the example of the demonstration task solution of the aerodynamic properties estimation for an unmanned aircraft with a high-aspect-ratio wing, the importance of taking into account the elastic deformations of the wing design at the initial design stages is shown. The integral and distributed aerodynamic characteristics of the wing of the aircraft are evaluated and compared with and without deformations.